2018
DOI: 10.1021/jacs.8b08605
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Catalyzed Radical Alkylation of Secondary and Tertiary Alkyl Chlorides Using Michael Acceptors

Abstract: Alkyl chlorides are common functional groups in synthetic organic chemistry. However, the engagement of unactivated alkyl chlorides, especially tertiary alkyl chlorides, in transition-metal-catalyzed C–C bond formation remains challenging. Herein, we describe the development of a TiIII-catalyzed radical addition of 2° and 3° alkyl chlorides to electron-deficient alkenes. Mechanistic data are consistent with inner-sphere activation of the C–Cl bond featuring TiIII-mediated Cl atom abstraction. Evidence suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 83 publications
1
81
0
Order By: Relevance
“…Our group previously demonstrated that secondary and tertiary alkyl chlorides could be reduced to alkyl radicals by Ti(III) catalysts. 34 Given that we have observed -chloroamides as by-products in the isomerization of aziridines, presumably via a Lewis acid mediated nucleophilic ring opening, we sought to assess the possibility of these chloroamides as key reactive intermediates (Scheme 4). Thus, we carried out two experiments using control substrates: a secondary chloroamide 4a and a tertiary chloroamide 4k (for details, see SI).…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…Our group previously demonstrated that secondary and tertiary alkyl chlorides could be reduced to alkyl radicals by Ti(III) catalysts. 34 Given that we have observed -chloroamides as by-products in the isomerization of aziridines, presumably via a Lewis acid mediated nucleophilic ring opening, we sought to assess the possibility of these chloroamides as key reactive intermediates (Scheme 4). Thus, we carried out two experiments using control substrates: a secondary chloroamide 4a and a tertiary chloroamide 4k (for details, see SI).…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…As the chloroalkenes feature high reduction potential ( E red < ‐2.0 V vs. SCE) an inner sphere SET can favour their direct reduction. In order to accomplish the desired transformation, Lin and co‐workers [ 33 ] have reduced the size of the titanium complex, employing Cp*Ti IV Cl 3 (Scheme 5). The favourable interaction of Cp*Ti III Cl with chlorine atoms allowed the generation of secondary and tertiary C‐centered radicals, which then were treated with different Michael acceptors.…”
Section: Tiiv/iii Catalysis With Stoichiometric Metallic Reductantsmentioning
confidence: 99%
“…[ 29 ] Cp 2 Ti III Cl is generated by reduction of commercially available Cp 2 Ti IV Cl 2 (stage a , Figure 1). The oxophilic Cp 2 Ti III Cl generally endorses the binding of hard Lewis bases (stage b , typically epoxides), but recent developments demonstrated the possibility to use other substrates such as enones, [ 30 ] nitriles, [ 31 ] N ‐acylaziridines, [ 32 ] chloroalkanes [ 33 ] and cyclopropyl ketones. [ 34 ] The key‐feature provided by the Ti center in titanocenes implies an inner‐sphere electron transfer from Ti III to the coordinated organic moiety (stage c ).…”
Section: Tiiv/iii Catalysis With Stoichiometric Metallic Reductantsmentioning
confidence: 99%
“…Inspired by the recent developments within radical chemistry, facilitated the commitment of regular functional groups (e.g., carboxylates, alcohols, alkenes, and alkanes) in carbon–carbon bond making reactions, a novel approach was developed by Lin group for Ti‐catalyzed alkylation of unactivated 2 o and 3 o alkyl chlorides with the optimized reaction conditions (Scheme ). Particularly, tertiary alkyl chlorides were effectively committed for the construction of C–C bond.…”
Section: Using Metal Catalysismentioning
confidence: 99%